Water Availability and Reliability in Dar es Salaam, Tanzania. Issue 9 (1st September 2016) - Smiley, Sarah L.
Abstract : Dar es Salaam, Tanzania's water landscape is unjust, inequitable, and uneven. Water rationing and electricity outages affect water availability alongside an overall shortfall in water supply. Using household surveys and interviews, this paper shows that a majority of respondents lack a consistently reliable source of water. To cope with poor access, households alter their daily routines, consume less water, and identify and use back-up sources of water. It is crucial to understand the problems of water availability in the city in order to make more informed policy decisions and more justly provide water access.